THE INFLUENCE OF E-WOM ON CUSTOMER PURCHASE DECISION OF THE COFFEE SHOPS AT JLN. FLAMBOYAN BY USING BRAND IMAGE AS MEDIATING VARIABLE - Lomanorek, Gabriela Abigail; Worang, Frederik G.; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study examines the influence of Electronic Word of Mouth (E-WOM) on customer purchase decisions for coffee shops located on Jln. Flamboyan, using brand image as a mediating variable. This research explores the extent to which E-WOM impacts brand image and how this, in turn, affects purchase decisions. A quantitative approach was employed, with data collected from 120 respondents through structured questionnaires. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that E-WOM has a significant positive impact on both brand image and purchase decisions. Moreover, brand image mediates the relationship between E-WOM and purchase decisions, demonstrating its crucial role in shaping consumer behavior. The findings underscore the importance of managing E-WOM and cultivating a strong brand image for coffee shops to influence customer purchase decisions effectively. The study provides practical insights for coffee shop owners on leveraging online reviews and enhancing brand perception to drive customer loyalty and business growth.   Keywords: E-WOM, Brand Image, Purchase Decision